1969
DOI: 10.21236/ad0860429
|View full text |Cite
|
Sign up to set email alerts
|

Candidiasis in Simians

Abstract: Lahoratory aiimIals Fungus Caindld.a athicbns Il 1st opathoIl I f•y DD .. " 473 'Ia "'AMM 1 w Unclassificed ' b i#,, C Iea5sg.e .. .

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

1977
1977
2019
2019

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 1 publication
0
9
0
Order By: Relevance
“…Disease Anorexia, dysphagia, open-mouth breathing due to ulcers of the hard palate, dehydration, and diarrhea are associated with candidiasis (Kaufmann and Quist, 1969b;Wikse et al, 1970;Weller, 1994). Onychomycosis, with shortening, erosion, and deformation of the nails, and balanitis have also been associated with candidiasis (Kerber et al, 1968;Wikse et al, 1970).…”
Section: Candidiasismentioning
confidence: 99%
“…Disease Anorexia, dysphagia, open-mouth breathing due to ulcers of the hard palate, dehydration, and diarrhea are associated with candidiasis (Kaufmann and Quist, 1969b;Wikse et al, 1970;Weller, 1994). Onychomycosis, with shortening, erosion, and deformation of the nails, and balanitis have also been associated with candidiasis (Kerber et al, 1968;Wikse et al, 1970).…”
Section: Candidiasismentioning
confidence: 99%
“…In fact, numerous studies have shown that nonhuman primates experience Candida species infections from similar predisposing factors as humans, including immunodeficiency [33][34][35]. Furthermore, rhesus macaques have been shown to have vaginal-associated Langerhans' cells, macrophages, and CD4 ϩ and CD8 ϩ T cells similar to those of humans [36,37].…”
mentioning
confidence: 99%
“…Candida albicans was isolated from tongue, liver, lung, and intestine. As suggested by Wikse et al [12], the pre valence of candidiasis in nonhuman primates probably exceeds that indi cated by published reports and it should be considered in the differential diagnosis of chronic upper respiratory and/or enteric disease.…”
Section: Pathologymentioning
confidence: 84%
“…In contrast, reports of lesions in nonhuman primates relatable to infection with Candida spp. are few and most are associated with other disease processes or anti bacterial prophylaxis [10,12]. The opportunistic nature of Candida spp.…”
Section: Introductionmentioning
confidence: 99%